2001
DOI: 10.1007/s00232-001-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of the S2 and S3 Segment in Determining the Activation Kinetics in Kv2.1 Channels

Abstract: We constructed chimeras between the rapidly activating Kv1.2 channel and the slowly activating Kv2.1 channel in order to study to what extent sequence differences within the S1-S4 region contribute to the difference in activation kinetics. The channels were expressed in Xenopus oocytes and the currents were measured with a two-microelectrode voltage-clamp technique. Substitution of the S1-S4 region of Kv2.1 subunits by the ones of Kv1.2 resulted in chimeric channels which activated more rapidly than Kv2.1. Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
3

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 28 publications
1
7
3
Order By: Relevance
“…The ‘normally functioning’ Kv1.2 channels in this study are actually quite dramatically different in many respects from Kv1.2 channels reported in the literature, expressed in Xenopus oocytes28. For example, the activation midpoint of Kv1.2 is −72 mV in the present study and −3.5 mV in oocytes28.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The ‘normally functioning’ Kv1.2 channels in this study are actually quite dramatically different in many respects from Kv1.2 channels reported in the literature, expressed in Xenopus oocytes28. For example, the activation midpoint of Kv1.2 is −72 mV in the present study and −3.5 mV in oocytes28.…”
Section: Discussioncontrasting
confidence: 93%
“…For example, the activation midpoint of Kv1.2 is −72 mV in the present study and −3.5 mV in oocytes28. The rate of activation in oocytes is slow compared to the present study to the extent that the currents are unrecognizable as being carried by the same channels.…”
Section: Discussioncontrasting
confidence: 71%
“…Activation time constants were estimated for each type by fitting an exponential curve to the rising phase; the two values, 1.69±0.04 and 1.03±0.13 ms for the delayed rectifier and the A-type, respectively, differ significantly (0.01 level). The delayed rectifier activation is considerably faster than in Kv 2.1 channels expressed in oocytes [19] , but the A-type time constant is close to the value measured in expressed Kv 4.3 [20] .…”
Section: Resultssupporting
confidence: 72%
“…Previous studies have demonstrated that the S3 segment of Kv2.1 channels could be important in determining the gating change and the activation kinetics of these channels (Koopmann et al, 2001;Li-Smerin and Swartz, 2001). In our study, chromanol 293B not simply altered the activation time course of I K ; however, it also produced a decrease in the effective gating charge.…”
Section: Discussionmentioning
confidence: 51%